Diversity and Morphological Characteristics of the Family Anacardiaceae in Percut Sei Tuan District, Deli Serdang Regency - Setiawan, Eka; Muliawati, Muliawati; Hasairin, Ashar (Universitas Negeri Medan, 2026)
The Anacardiaceae family holds significant ecological and economic value in tropical Asia, including Indonesia, as a source of fruits, timber, and valuable secondary metabolites. This study aimed to identify and describe the species diversity and morphological characteristics of Anacardiaceae in Percut Sei Tuan District, Deli Serdang Regency. The research was conducted from December 2025 to February 2026 using a descriptive exploratory method involving field observation, specimen collection, and morphological analysis. Sampling followed the exploration method of Rugayah et al., while morphological observations were based on de Vogel and Rifai. Species identification was conducted using taxonomic literature from the Anacardiaceae series of Flora Malesiana and herbarium specimens. The results recorded five species of Anacardiaceae: Mangifera indica, Mangifera odorata, Mangifera foetida, Anacardium occidentale, and Spondias dulcis. Mangifera indica was the most dominant species, comprising seven cultivated cultivars. Species differentiation was based on vegetative and generative morphological traits, including leaf type, shape, apex, texture, inflorescence type, fruit, and seed characteristics. The findings indicate relatively high diversity of Anacardiaceae in the study area, particularly within the genus Mangifera, influenced by environmental variation and human cultivation practices.